Analisis kinerja keuangan perusahaan dengan menggunakan metode Economic Value Added (EVA) pada perusahaan ritel yang terdaftar di Bursa Efek Indonesia (BEI) periode 2020 - 2022 - Lukas, Tania Christin; Saerang, David P. E.; Maradesa, Djeini (Manajemen Bisnis dan Keuangan Korporat, 2025)
This research aims to measure and calculate the company's financial performance using the EVA method and to assess the company's ability to generate economic value added for the company and investors. The research method used is descriptive quantitative research, utilizing quantitative data types and sources, specifically secondary data obtained from the official website of the Indonesia Stock Exchange (IDX). The analysis of the company's financial performance in this study uses the Economic Value Added (EVA) method, which measures or assesses the company's ability to generate economic value added. Based on the research results using the EVA method, PT. Sumber Alfaria Trijaya Tbk and PT. Matahari Putra Prima Tbk in 2020 generated positive EVA values (EVA > 0). Meanwhile, in 2021 and 2022, they produced negative EVA values (EVA < 0). PT. Hero Supermarket Tbk and PT. Supra Boga Lestari in 2020 and 2021 generated negative EVA values (EVA < 0). Whereas in 2022, it generated a positive EVA (EVA > 0). PT. Midi Utama Indonesia Tbk in the years 2020 – 2022 generated negative EVA values (EVA < 0). Based on the EVA analysis results, if EVA is positive (EVA > 0), it means the company can create economic value added, so the company's financial performance can be said to be running well. Whereas if EVA is negative (EVA < 0), it means the company is unable to generate economic value added, so the company's financial performance can be said to be not running well as expected by the company.